Increased levels of lysosomal cysteinyl cathepsins in human varicose veins: a histology study - Xu, Na; Zhang, Yuan-Yuan; Lin, Yan; Bao, Bin; Zheng, Lei; Shi, Guo-Ping; Liu, Jian (Thrombosis and haemostasis, 2014)
Varicose veins are a major chronic venous disease characterised by extensive remodelling of the extracellular matrix architecture in the vascular wall. Although matrix metalloproteinases have been implicated in these pathologic events, little is known about the functional relevance of other protease family members. Here, we studied the distribution of lysosomal cysteine proteases, cathepsins B, L, K, and S, and their endogenous inhibitor, cystatin C, in long saphenous vein specimens from nine normal donors and 18 patients with varicose veins (VVs). Immunohistochemical analysis demonstrated increased levels of cathepsins L, K, B, and S and reduced levels of cystatin C in VVs. This imbalance between cysteinyl cathepsins and cystatin C may favour VV remodelling. To investigate the inflammatory mechanism of their expression, we examined a detailed inflammatory cell profile in VVs, including macrophages, T lymphocytes, and mast cells. Increased numbers of CD3-positive T cells and tryptase-positive mast cells were found in VVs, and enhanced levels of cysteinyl cathepsins were detected from lesion CD3-positive T cells, chymase-positive mast cells, endothelial cells, and smooth-muscle cells. Elevated cathepsins, and their co-localisation to infiltrated inflammatory cells and to vascular cells, suggest that these proteases participate in extracellular matrix degradation in response to inflammation during VV pathogenesis.